Doxorubicin nanoformulations on therapy against cancer: An overview from the last 10 years - D'Angelo, Natália A.; Noronha, Mariana A.; Câmara, Mayra C.C.; Kurnik, Isabelle S. [UNESP]; Feng, Chuying; Araujo, Victor H.S. [UNESP]; Santos, João H.P.M.; Feitosa, Valker; Molino, João V.D.; Rangel-Yagui, Carlota O.; Chorilli, Marlus [UNESP]; Ho, Emmanuel A.; et al. (Elsevier, 2022)
Doxorubicin (DOX) is a natural antibiotic with antineoplastic activity. It has been used for over 40 years and remains one of the most used drugs in chemotherapy for a variety of cancers. However, cardiotoxicity limits its use for long periods. To overcome this limitation, encapsulation in smart drug delivery systems (DDS) brings advantages in comparison with free drug administration (i.e., conventional anticancer drug therapy). In this review, we present the most relevant nanostructures used for DOX encapsulation over the last 10 years, such as liposomes, micelles and polymeric vesicles (i.e., polymersomes), micro/nanoemulsions, different types of polymeric nanoparticles and hydrogel nanoparticles, as well as novel approaches for DOX encapsulation. The studies highlighted here show these nanoformulations achieved higher solubility, improved tumor cytotoxicity, prolonged DOX release, as well as reduced side effects, among other interesting advantages.
Keywords: Cancer therapy; Chemotherapy; Doxorubicin (DOX); Drug delivery systems (DDS); Drug encapsulation; Nanostructures (Ns)